Morphological and Genetic Identification of Head Taunsa Barrage Fish Species - Naz, Saima; Chatha, Ahmad Manan Mustafa; Nazir, Urooj; Iqbal, Syeda Saira; DANABAS , Durali (Current Trends in OMICS, 2023)
The current study aims to construct a thorough barcoding reference database of fishes in the Head Taunsa Barrage and assess the usefulness of employing the COI gene for fish species identification. A total of 15 genera, 10 families, and 7 orders of fish were used to collect a total of 19 mitochondrial COI barcode sequences. These sequences had an average length of 800 base pairs. Within species, genera, families, orders, and classes, the average Kimura two-parameter (K2P) distances were 0.97%, 0.99%, 1.23%, and 1.26%, respectively. According to their taxonomic classification, species were commonly clustered in the K2P neighbor-joining trees based on the sequence. DNA barcoding was employed in this study to identify species with a high degree of accuracy. Moreover, it was concluded that COI sequencing can be used to recognize fish species.